High-risk behaviours and concomitant medical illnesses among patients at Methadone Maintenance Therapy Clinic, Hospital Tengku Ampuan Afzan, Malaysia - Musa, Ramli; Mat Zin, Nora; Abu Bakar, Zafri; Mohd Rozali, Junid; Ali Khan, Umeed; Maung Ko, Ismail (Academy of Family Physicians of Malaysia, 2009)
Background: High prevalence of high-risk behaviours and concurrent medical illnesses among opioid drug users would influence the outcome of Methadone Maintenance Programme. It would also require a special medical attention to contain these issues. Objectives: This study explored patients’ characteristics and their high-risk behaviours in order to understand more about opioid dependent users in Malaysia. Methods: A total of 172 patient case notes at Methadone Clinic Hospital Tengku Ampuan Afzan (HTAA) were retrieved for relevant data. Results: Many of the patients were engaged in high-risk behaviours such as needle sharing, unsafe sex and criminal activities. A large number of the subjects had contracted blood-borne diseases such as HIV and hepatitis infections. Conclusions: Education on the issue of medical and psychosocial complications related to high risk behaviours is essential. Medical professionals dealing with this group have to pay attention and update their knowledge on the medical issue. Keywords: Methadone therapy, opioid dependence, high-risk behaviours.